2019
DOI: 10.3389/fnins.2019.00859
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Activates Autophagy via the AKT/mTOR Signaling Pathway to Improve Cognitive Dysfunction in Rats With Chronic Cerebral Hypoperfusion

Abstract: Chronic cerebral hypoperfusion (CCH) is a main cause of vascular dementia and is also an etiological factor of neurological diseases and mental disorders. However, few treatments are available for CCH, and new medications are needed. In the present study, we employed a rat model of CCH that was based on bilateral common carotid artery occlusion and investigated the therapeutic effects of resveratrol and its detailed mechanism of action. We evaluated neurological deficit scores and performed the Morris water ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 51 publications
(50 reference statements)
1
49
0
Order By: Relevance
“…Delayed degeneration of these neurons caused by global ischemia results in cognitive deficits. Neuronal degeneration and memory deficits caused by CCH have been extensively reported [7,30]. Consistently, we have previously found that neuronal injury and cognitive impairment are prominent at 8 weeks following BCCAO [18].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Delayed degeneration of these neurons caused by global ischemia results in cognitive deficits. Neuronal degeneration and memory deficits caused by CCH have been extensively reported [7,30]. Consistently, we have previously found that neuronal injury and cognitive impairment are prominent at 8 weeks following BCCAO [18].…”
Section: Discussionsupporting
confidence: 88%
“…Recently, a number of mechanisms thought to underlie cognitive dysfunction caused by CCH, including white matter impairment, oxidative stress and neuroinflammation, among which neuroinflammation plays a primary role in the pathophysiology of VaD [6,7]. Neuroinflammation is mainly manifested by microglial activation and subsequent release of inflammatory factors, ultimately leading to brain tissue damage.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of compounds which are mostly investigated for their potential neuroprotective effects include quercetin, kaempferol and myricetin (flavonols) [ 50 , 51 , 52 , 53 , 54 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ], scutellarin, baicalein, and apigenin (flavones) [ 50 , 55 , 56 , 61 , 87 , 88 , 89 , 90 ], catechins, epicatechin, and epigallocatechin gallate (EGCG, flavanols), as well as genistein (isoflavonoid), and silymarin (flavonolignan) [ 63 , 91 , 92 , 93 , 94 , 95 , 96 ]. The stilbene group is best exemplified by resveratrol, a well-known phenolic compound found in red wine, grape, and virgin olive oil, which has shown remarkable neuroprotective and anti-aging properties in a plethora of experimental models [ 50 , 58 , 59 , 65 , 69 , 97 , 98 , 99 , 100 , 101 , 102 ]. Finally, phenolic acids, which can be subdivided into hydroxybenzoic acids (such as syringic and gallic acids) [ 103 ,…”
Section: An Overview Of Neuroprotective Phytochemical Classesmentioning
confidence: 99%
“…In this frame, it is remarkable that the common neuroprotective, antioxidant, and anti-inflammatory effects produced by several phytochemicals are associated with rescuing autophagy, meanwhile counteracting behavioral alterations, mitochondrial damage as well as intracellular accumulation and release of potentially detrimental substrates [ 3 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. As recently reviewed, the neuroprotective effects of phytochemicals involve also a double-faceted, yet controversial modulation of the proteasome pathway, which will not be discussed in detail herewith [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…40 rats were randomly classified into three groups: Sham operated Group (13 rats), MDP Group (14 rats) and Model Group (13 rats) according to a Random Number Table. BCCAO can definitely prepare CCH model rats whose cognitive impairment were testified by MWM test [12,13]. The CCH models (including Model Group and MDP Group) were made by a modified BCCAO method which was carried out in two steps: Rats' left and right common carotid artery were ligated separately one week apart.…”
Section: Preparation Of Cch Model and Intervention Measuresmentioning
confidence: 99%